2014
DOI: 10.1177/1460458213518545
|View full text |Cite
|
Sign up to set email alerts
|

Electronic patient information systems and care pathways: The organisational challenges of implementation and integration

Abstract: Our interest here is with the 'marriage' of e-patient information systems with care pathways in order to deliver integrated care. We report on the development and implementation of four such pathways within two National Health Service primary care trusts in England: (a) frail elderly care, (b) stroke care, (c) diabetic retinopathy screening and (d) intermediate care. The pathways were selected because each represents a different type of information and data 'couplings', in terms of task interdependency with so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 26 publications
(44 reference statements)
0
28
0
1
Order By: Relevance
“…Frustration with information technology (IT) systems was frequently reported in the UK qualitative literature. 72,94,95,100,102,105,107,110,118,124,126,134,146,149 A lack of compatibility between systems used in different services, such as health and social care or general practices and hospitals, was a key barrier to integrated working. 94,95,102 In one study, 100 over half of the clinicians (56%) reported that they were dissatisfied with IT systems.…”
Section: Information Technology and Logisticsmentioning
confidence: 99%
“…Frustration with information technology (IT) systems was frequently reported in the UK qualitative literature. 72,94,95,100,102,105,107,110,118,124,126,134,146,149 A lack of compatibility between systems used in different services, such as health and social care or general practices and hospitals, was a key barrier to integrated working. 94,95,102 In one study, 100 over half of the clinicians (56%) reported that they were dissatisfied with IT systems.…”
Section: Information Technology and Logisticsmentioning
confidence: 99%
“…Some recent studies have focused on the use of these new technologies in order to offer patients with mobility difficulties integrated care by pooling electronic records from patients, caregivers or healthcare teams as well as doctors' follow-ups [82]. However, the implementation of such processes requires considerable organisation and adequate resources [83] and can lead to technical interoperability problems [84].…”
Section: Resultsmentioning
confidence: 99%
“…Kommunenes valgfrihet påvirkes også av tidligere teknologiske løsninger. Dette kan forstås som en form for stiavhengighet der tidligere valg påvirker dagens muligheter ved å legge føringer og begrensinger (Dent & Tutt, 2014). Et eksempel på dette er hvordan valg av elektronisk pasientjournalsystem tatt mange år tilbake, i dag legger føringer på hvilke velferdsteknologiske løsninger kommunene kan velge.…”
Section: Sammenkobletunclassified